INVERSE VERTICAL RATIO PUT SPREAD STRATEGY AND ITS APPLICATION IN HEDGING AGAINST A PRICE DROP - ŠOLTÉS, Vincent; AMAITIEK, Omer Faraj S. (Journal of Advanced Studies in Finance, 2010)
The paper proposes a generalization of a strategy known as the Long Two Buy One Ratio Put or Put Backspread Strategy. Moreover, it proposes an application of the strategy in hedging against a price drop of the underlying asset to a future date in a way which enables hedging with zero cost. We have found a profit function, as well as a function of income from a hedged position in the analytical form, which simplifies the application in particular hedging.